2012
DOI: 10.1021/pr201253h
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Chromatography–Mass Spectrometry Based Metabolomics Study of Cloned versus Normal Pigs Fed Either Restricted or Ad Libitum High-Energy Diets

Abstract: Genetically identical cloned pigs should in principle eliminate biological variation and provide more pronounced effects when subjected to, e.g., dietary interventions, but little is known about how phenotype and phenotypic variation is affected by cloning. Therefore, an investigation of the metabolome of cloned pigs compared to normal control pigs was performed to elucidate the variation and possible differences in the metabolic phenotypes during a dietary intervention. A total of 19 control pigs and 17 clone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 44 publications
4
23
0
Order By: Relevance
“…After weaning all the pigs received a standard pig diet with an energy distribution of 18.5% protein, 7.9% fat, 72.4% carbohydrate and 1.2% fiber, until the cloned pigs were 22 weeks old and the non-cloned pigs were 19 weeks old. After this period, the pigs were housed individually and fed a wheat-based high-fat-high-energy (HF/HE) experimental diet consisting of 19.5% protein, 27% fat, 53% carbohydrates and 0.5% fiber, 28 in restricted amounts for approximately 21 weeks. The lean group of pigs received the same diet as the pigs in the obese group (ad libitum) but restricted to 60% of the feed consumed by the ad libitum group.…”
Section: Animalsmentioning
confidence: 99%
“…After weaning all the pigs received a standard pig diet with an energy distribution of 18.5% protein, 7.9% fat, 72.4% carbohydrate and 1.2% fiber, until the cloned pigs were 22 weeks old and the non-cloned pigs were 19 weeks old. After this period, the pigs were housed individually and fed a wheat-based high-fat-high-energy (HF/HE) experimental diet consisting of 19.5% protein, 27% fat, 53% carbohydrates and 0.5% fiber, 28 in restricted amounts for approximately 21 weeks. The lean group of pigs received the same diet as the pigs in the obese group (ad libitum) but restricted to 60% of the feed consumed by the ad libitum group.…”
Section: Animalsmentioning
confidence: 99%
“…Surviving cloned pigs are generally found to be healthy and production and reproduction properties in adult cloned pigs are generally normal; however, there are several reports of cloned pigs having deviant phenotypes. These include pulmonary hypertension and other hemodynamic disorders, contracted foreleg tendons, and respiratory problems (Whyte et al, 2011), changes in metabolic phenotype (Christensen et al, 2012;Clausen et al, 2011), and a higher incidence of mild atelectasis (Park et al, 2011). Lower body weight is a common finding in cloned pigs, both at birth and later (Archer et al, 2003;Jiang et al, 2007;Park et al, 2011;Tian et al, 2008), although it is not always observed (Carter et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (Lee et al, 2009) have shown a high number of significant differences in blood parameters of obese Ossabaw pigs compared to lean pigs with significantly elevated levels of total cholesterol (p = 0.03) and triglycerides (p = 0.02) (and insulin, though not significantly, p = 0.10). According to Christensen et al (2012) the only obesity feature affected in domestic pig is total cholesterol (p = 0.01) and in the Göttingen minipigs the only obesity feature affected by obesity was fasting insulin (Moesgaard et al, in preparation). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They were all female and reared and housed in the same experimental stables of Aarhus University (Tjele, Denmark). At three months of age the pigs were fed a high-energy diet (containing 10% sugar and 10% soy oil, as described by Christensen et al (2012)) ad libitum (obese, n = 10) or at 60% intake (lean, n = 9). At 8-9 months the pigs were euthanized and tissue samples from liver, abdominal s.c. adipose tissue (SAT) (a combination of deep and superficial SAT), mesenteric fat surrounding the appendix (VAT) and s.c. fat from the neck (neck SAT) were obtained and snap frozen in liquid nitrogen, and blood was collected for serum preparation.…”
Section: Methodsmentioning
confidence: 99%